2017
DOI: 10.1021/acsami.7b07650
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Graphene Foam-Filled Elastomer Composites with High Thermal and Mechanical Properties

Abstract: To meet the increasing demands for effective heat management of electronic devices, a graphene-based polymeric composite is considered to be one of the candidate materials owing to the ultrahigh thermal conductivity (TC) of graphene. However, poor graphene dispersion, low quality of exfoliated graphene, and strong phonon scattering at the graphene/matrix interface restrict the heat dissipation ability of graphene-filled composites. Here, a facile and versatile approach to bond graphene foam (GF) with polydimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(100 citation statements)
references
References 60 publications
5
95
0
Order By: Relevance
“…A number of studies have shown that most properties of composite materials depend on the nanoparticles dispersion in polymer matrix and their interfacial interaction [13][14][15]. Therefore, there are numerous examples have been proposed for improving the dispersion of nanoparticles in polymer matrix thus improving the interfacial interactions by grafting or surface modified materials on the surface of nanoparticles for functionalization [16][17][18]. Meanwhile, effects of surface structure of nanomaterials on the properties of composites are still the focus of research [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that most properties of composite materials depend on the nanoparticles dispersion in polymer matrix and their interfacial interaction [13][14][15]. Therefore, there are numerous examples have been proposed for improving the dispersion of nanoparticles in polymer matrix thus improving the interfacial interactions by grafting or surface modified materials on the surface of nanoparticles for functionalization [16][17][18]. Meanwhile, effects of surface structure of nanomaterials on the properties of composites are still the focus of research [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Lots of energy can be absorbed by GN when the strain occurred, leading to the improvement of Young's modulus and tensile strength [34]; (3) graphene tube has smaller elongation at break compared with PDMS. Once the fracture of GNs happened, the graphene tube propagated either along the interface, or into the PDMS matrix to cause final failure, resulting in the decrease of elongation at break of PDMS [37].…”
Section: Resultsmentioning
confidence: 99%
“…Lots of energy can be absorbed by GN when the strain occurred, leading to the improvement of Young's modulus and tensile strength [34]; (3) graphene tube has smaller elongation at break compared with PDMS. Once the fracture of GNs happened, the graphene tube propagated either along the interface, or into the PDMS matrix to cause final failure, resulting in the decrease of elongation at break of PDMS [37]. We have also conducted 100 stretching and release cycles to 100% tensile strain on the composite, and the composite shows a moderate decrease (<13%) in the stress required to deform it to this strain level at the 100th cycle (Figure 6b), indicating that the composite is intact for up to 100 stretching and release cycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of composites and their corresponding PDA/APTS modification were analyzed via tensile tests by Bai et al (Fang et al 2017). The typical stress-strain curves are shown in Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%